2001
DOI: 10.1007/bf02255946
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of dengue virus infection

Abstract: Dengue virus infection causes dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS), whose pathogeneses are not clearly understood. Current hypotheses of antibody-dependent enhancement, virus virulence, and IFN-gamma/TNFalpha-mediated immunopathogenesis are insufficient to explain clinical manifestations of DHF/DSS such as thrombocytopenia and hemoconcentration. Dengue virus infection induces transient immune aberrant activation of CD4/CD8 ratio inversion and cytokine overproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
228
3
33

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(271 citation statements)
references
References 67 publications
7
228
3
33
Order By: Relevance
“…26 Liver dysfunction might be responsible for the decreased synthesis of specifi c factors of the intrinsic pathway, an unbalance of which may consequently cause hemorrhage. 26 In our fi nding, mean values of both the transaminases were signifi cantly raised in all four serotype groups, when compared with control groups. Elevation of liver aminotransferase levels was maximum in Den-2 patients (app.…”
Section: Discussionmentioning
confidence: 99%
“…26 Liver dysfunction might be responsible for the decreased synthesis of specifi c factors of the intrinsic pathway, an unbalance of which may consequently cause hemorrhage. 26 In our fi nding, mean values of both the transaminases were signifi cantly raised in all four serotype groups, when compared with control groups. Elevation of liver aminotransferase levels was maximum in Den-2 patients (app.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs as a result of both reduced production and increased destruction of platelets. [107][108][109] It has been suggested that the degree of thrombocytopenia correlates with clinical severity and complement activation. 110 As a result of reduced platelet counts and increased complement activation there is increased vascular fragility and thus an increased risk of haemorrhage.…”
Section: Thrombocytopeniamentioning
confidence: 99%
“…112 Elevations of IL-6 and IL-8 have been associated with disordered coagulation and fibrinolysis in dengue. 109,111 Data from children in Vietnam has shown that increased APTT and reduced fibrinogen are consistently observed in patients with dengue. 113 The same study showed minor elevations in prothrombin time (PT).…”
Section: Coagulopathymentioning
confidence: 99%
“…Liver is one of the target organs of dengue virus, and it can be diagnosed hepatomegaly and an increased hepatic protein in serum after infection 14 , therefore, by the range release of inflammatory mediators such as cytokines, which can both protect and damage the body according to individual variations or numbers of infections 17 . These are able to perform their actions by acting on specific receptors present in the membranes of the target cells.…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%